Mysterious Dequervain Tenosynovitis in A Knitting Housewife With Pain Neuroscience Education: A Case Report - Kumar Singh, Krishna; Sharma, Nidhi Suresh; Bante, Divya; Waghmare, Preeti; Charate, Shubhangi (Journal of Neonatal Surgery, 2025)
Introduction: Muscles near the base of the thumb, the abductors pollicis longus (APL) and extensor pollicis brevis (EPB), increase when de Quervain tenosynovitis occurs. This disease is extremely uncomfortable and aggravating. Due to extended ignorance and neglect, the patient often has pain and discomfort that interferes with and limits their ability to perform everyday tasks. In many situations, late finding results in an increase in inflammation. Case Description: A 56-year-old women reported that her right wrist and thumb ached. On top of that, she says that she feels pain when performing her daily tasks. Prior to the onset of progressive soreness in her right thumb three months ago, she appeared to be doing well. Knitting has been her favourite way for more than a decade. The combination of conservative treatment approach consisted of strengthening with patient education and traditional pain neuroscience education. Outcome measures including NPRS and PRWE, Pain Catastrophization scale, Hamilton depression scale, Finklestine test. Patient symptoms resolved in 8 weeks and follow up reported no recurrence of wrist pain. Conclusion: In the current case report, PNE was added to the conventional treatment for Dequervain tenosynovitis, and the patient's overall activity level and stress levels improved. PNE increases patient awareness and knowledge of the current situation and helps reduce discomfort and the tendency to categorize it.